Formulation of Eel (Monopterus albus) extract membranes for wound dressing using plasticizers - Febriyenti Febriyenti; Rahmi Nofita; Khalidazia Khalidazia (Fakultas Farmasi Universitas Andalas, 2020)
The types of wound dressing will affect wound healing processes. The membrane is one of the potential wound dressing that can maintain the moisture of the wound surface. The eel extract as an active ingredient could be added to the membrane formula to accelerate wound healing. This study aimed to formulate eel (Monopterus albus) extract membranes for wound dressing using some plasticizers. Polyvinyl alcohol (PVA) 146,000 was used as the polymer, while glycerol, propylene glycol,and polyethylene glycol (PEG) 400 were used as the plasticizers. Methylparaben and propylparaben were added as preservatives. Evaluations included thickness, water vapor permeability, and mechanical properties of the membranes that consisted oftensile strength, elongation at break, and Young's modulus were performed. The result showed that the use of different types of plasticizers affected the mechanical properties of the eel extract membrane. The formula that used glycerol as the plasticizer produced membranes with the best water vapor permeability and mechanical properties.